Infected Osteoclastoma of the Knee: An Unusual Presentation - O. B. Pattanashetty; B. B. Dayanand; Yogesh Mapari; Monish Bami (Case Reports in Oncological Medicine)
Introduction. Giant cell tumor is a benign or locally aggressive tumor of uncertain origin that appears in mature bone, most commonly in the distal femur, proximal tibia which characteristically extends right up to the subarticular bone plate. Case Report. We report here a 35-year-old female presenting with swelling of the left knee. On examination, the swelling was solitary, about 20 × 15 cm in size with the skin over the swelling stretched and glistening. On the fifth day of hospital stay, the swelling burst open and blood tinged pus started pouring out. X-ray and MRI scan showed a well-defined T2 hyperintense expansile eccentrically located osteolytic lesion involving the metaphyseal region of the proximal tibia and extending into the subarticular space and multiple T1/T2 hypointense septations are noted within the lesion suggestive of osteoclastoma. The patient was counseled regarding the tumor and prognosis and various treatment options. She was treated successfully with above knee amputation. The tissue was sent for histopathology which confirmed osteoclastoma. Conclusion. It is important to recognize giant cell tumors early, so that they can be treated promptly with local measures to prevent morbidity and mortality in young adults.